An Empirical Investigation of Stockholder Reaction to Disclosures Required by ASR No. 250 - Glezen, G. William; Millar, James A. (Journal of Accounting Research, 1985)
G. William Glezen, James A. Millar, An Empirical Investigation of Stockholder Reaction to Disclosures Required by ASR No. 250, Journal of Accounting Research, Vol. 23, No. 2 (Autumn, 1985), pp. 859-870